PERAN GURU PAI DALAM MENANAMKAN SIKAP MODERASI SISWA DI UPT SMPN 17 GRESIK - Khulaefatur Rosidah; Ali Ahmad Yenuri (JOURNAL SAINS STUDENT RESEARCH, 2026)
Religious moderation is a way to maintain harmony among different religious communities. Amid various conflicts between religions in today's life, the role of Islamic religious education teachers is very effective in introducing moderation to students so that they can have a moderate attitude in national and societal life. It is not only introduced but also exemplified so that students can practice it in their daily lives. This study uses a qualitative research approach. With this type of field research, the results show that the role of teachers is not only to broaden students' understanding of religious moderation but also to guide them to behave according to religious norms and to regulate students' behavior without creating any obvious differences.